An Attempt at the Classification of a Quarter of (Non-Critical) Corporate Social Reporting - Woodward, David G (Accounting Department,, 1998)
Whilst corporate social responsibility (CSRes hereafter) perhaps has a long history, corporate social reporting (CSRep hereafter) is probably of more recent origin. Thus although Guthrie and Parker (1989) were able to show in their longitudinal study of Broken Hill Proprietary eyidence of CSRep activity (as revealed via the company's annual reports), going back to the last century, such studies remain a rarity (although see also Hogner 1982; and Niemark 1992).The major early developments in the field of CSRep seem to have occurred in the USA in the earlv 1970s. with the emergence of two parallel initiatives.Firstly, there was the development of what might be called generalised models of CSRep. These were m some cases highly theoretical and exhibited great difficulty of application to real life organisations